Haptic control of steer-by-wire systems for tracking of target steering feedback torque. (April 2020) - Lee, Jaepoong; Yi, Kyongsu; Lee, Dongpil; Jang, Bongchoon; Kim, Minjun; Hwang, Sangwoo
This study proposes a haptic control of steer-by-wire systems for tracking a target steering feedback torque to achieve the conventional steering feedback torque. The haptic feedback control with a steer-by-wire steering-wheel system model was used to provide drivers with a conventional steering feedback torque. The steer-by-wire steering-wheel system model was developed, and a haptic control algorithm was designed for a desired steering feedback torque with a three-dimensional target steering torque map. In order to track the target steering torque to let the drivers feel the conventional steering efforts, an adaptive sliding-mode control was used to ensure robustness against parameter uncertainty. The angular velocity and angular acceleration used in the control algorithm were estimated using an infinite impulse response filter. The performance of the proposed controller was evaluated by computer simulation and hardware-in-the-loop simulation tests under various steering conditions. The proposed haptic controller successfully tracked the steering feedback torque for steer-by-wire systems.